Patron Offending and Intoxication in Night Time Entertainment Districts (POINTED): A Study Protocol - Miller, Peter; Pennay, Amy; Jenkinson, Rebecca; Droste, Nicolas; Chikritzhs, Tanya; Tomsen, Stephen; Wadds, Phillip; Jones, Sandra; Palmer, Darren; Barrie, Lance; Lubman, Dan (Kettil Bruun Society for Epidemiological Research on Alcohol (KBS), 2013)
Risky alcohol consumption is the subject of considerable community concern in Australia and internationally, particularly the risky drinking practices of young people consuming alcohol in the nighttime economy. This protocol paper describes a study that will determine some of the factors and correlates associated with alcohol-related risk taking, offending and harm in and around licensed venues and nighttime entertainment precincts across five Australian cities (three metropolitan and two regional). The primary aim of the study is to measure levels of pre-drinking, drinking in venues, intoxication, illicit drug use and potentially harmful drinking practices (such as consuming shots or mixing alcohol with energy drinks) of patrons in entertainment areas, and to relate this activity to offending, risky behavior and harms experienced. The study will also investigate the effects of license type, trading hours, duration of drinking episodes and geographical location on intoxication, offending, risk taking and experience of harm. Data collection involves patron interviews (incorporating breathalysing and drug testing) with approximately 7,000 people attending licensed venues. Intensive venue observations (n = 112 individual sessions) will also be undertaken in a range of venues, including pubs, bars and nightclubs. The information gathered through this study will inform prevention and enforcement approaches of policy makers, police and venue staff.